A LINGUOPRAGMATIC ANALYSIS OF POLITENESS STRATEGIES IN ENGLISH AND UZBEK LANGUAGES - Rustamova Mohinabonu Sherzod qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores the linguopragmatic features of politeness strategies in English and Uzbek languages. It investigates how cultural values and social hierarchy and communicative contexts shape the use of politeness expressions in both linguistic communities. The study draws on the theories of Brown and Levinson, Leech and Grice to analyze linguistic forms and pragmatic meanings that express politeness. Comparative analysis reveals that while English communication emphasizes individual autonomy and indirectness, Uzbek speech patterns reflect collectivist values, respect and social harmony. The findings highlight the importance understanding cross-cultural politeness strategies to enhance intercultural communication and translation accuracy.